CALCIUM AND INORGANIC PHOSPHORUS IN THE BLOOD OF RABBITS : IV. INFLUENCE OF LIGHT ENVIRONMENT ON NORMAL RABBITS. - Brown, Wade H. (The Rockefeller University Press, 1929)
A series of experiments was carried out for the purpose of determining whether a light environment comprising radiations of comparatively long wave-length and only a small amount of energy was capable of affecting the chemical equilibrium of the blood as indicated by the calcium and inorganic phosphorus content of the blood of normal rabbits. A study was made of effects produced by prolonged exposure to fixed environmental conditions (neon light and darkness) as compared with a varying environment of diffuse, filtered sunlight and by a change from one environment to another. It was found that the chemical equilibrium of the blood was definitely affected by the conditions employed and that the effects produced could be correlated with differences in organic constitution on the one hand, and on the other, with certain differences in the functional activity of the same animals, involving nutrition and growth and the proliferative activity of hair follicles.